Effects of Ga and Sn on the electrochemical behavior of Mg–6Al–1Zn as anode materials. Issue 8 (26th February 2020) - Wan, Xiaofeng; Chen, Wei; Zhou, Jingling; Zhang, Hua; Zhang, Fubao; Wei, Kequan
Abstract: The microstructure and electrochemical behavior of Mg–6Al–1Zn, Mg–6Al–1Zn–1Ga, Mg–6Al–1Zn–1Sn, and Mg–6Al–1Zn–0.5Sn–0.5Ga as anode materials in a 3.5 wt% NaCl solution are compared systematically. The results show that Sn alloying refines the second‐phases of Mg–6Zn–1Al by promoting tiny granular Mg17 Al12 phases containing Sn, and inspires their disperse distribution. However, the Ga results in the formation of semicontinuous reticular Ga containing Mg17 Al12 phases. The comparison of discharge tests indicates that Mg–6Al–1Zn–1Sn has the highest discharge activity, and Mg–6Al–1Zn–1Ga displays the largest hydrogen evolution corrosion resistance in 3.5 wt% NaCl solution at 298 K. The synergy of Ga and Sn can shorten discharge activation time and promote low discharge potential. In addition, the utilization efficiencies of the alloys decrease as follows: Mg–6Al–1Zn–1Ga > Mg–6Al–1Zn–0.5Sn–0.5Ga > Mg–6Al–1Zn–1Sn > Mg–6Zn–1Al. This study illustrates that the Mg–6Al–1Zn–0.5Sn–0.5Ga alloy has acceptable utilization efficiency and desirable electrochemical activity, which implies that doping Ga and Sn obtains a balance between discharge activity and utilization efficiencies. Abstract : The electrochemical behaviors of Mg–6Al–1Zn based anodes are compared in 3.5 wt% NaCl solution at 293 K. The results indicate that Mg–6Al–1Zn–1Sn has the highest discharge activity, and doping Ga displays the enhanced hydrogen evolution corrosion resistance. The synergy of Ga and Sn can obtain a balance between discharge activity and utilization efficiencies.